Sunflowers in the Ruins: A Multimodal Analysis of the Environmental Aspects of Ukrainian War Songs from February to May 2022 - Andrianova, Anastassiya (East/West, 2024)
This paper looks at the depiction of nature and the environment in contemporary Ukrainian anti-war music videos, inspecting the videos through an ecocritical and ecomusicological lens—and thus adding an environmental dimension to the existing scholarship on Ukrainian music. My goal is to call attention to the long-term impacts of the Russo-Ukrainian war on the non-human by exploring the ways in which landscapes and other features of nature are communicated multimodally. I accomplish this by examining a digital archive of music videos by Ukrainian artists that were uploaded to YouTube between February and May 2022. The music-video archive is placed in the context of Ukrainian environmental history, ecological awareness, and climate denialism before and after Ukraine’s 1991 independence. I apply a method of multimodal discourse analysis to this digital archive of compositions, which vary in genre (rap; rock; ethno-pop) and viewer impact (from thousands to millions of YouTube views). Most of them feature war footage that foregrounds industrial, residential, and natural devastation, while their lyrics and/or visuals include natural elements, such as spring (the literal and metaphoric countermeasure to the February 2022 invasion); the sun or its absence; sunflowers; and non-human animals. Some of the videos include war footage contrasted with aerial sequences of Ukraine’s pre-war cultural and natural diversities. Two videos imaginatively erase war devastation using a reverse-action technique. Without diminishing the pressing need for national resurgence and the emotional and affective function of music in providing hope for an imminent victory, I propose a more long-term, ecological approach: to resist the desire to return to an idealized pre-war past, and instead to discover new modes of living that take into account the precarity of postwar ecologies.